Observer design for rectangular descriptor systems with incremental quadratic constraints and nonlinear outputs—Application to secure communications. (19th September 2020) - Moysis, Lazaros; Gupta, Mahendra Kumar; Mishra, Vikas; Marwan, Muhammad; Volos, Christos
Summary: This work considers the problem of observer design for rectangular descriptor systems with nonlinearities satisfying incremental quadratic constraints. The observer design is feasible under the satisfaction of a linear matrix inequality and some algebraic relations in the system matrices. The special case of nonlinearities in the output is also considered. Finally, the developed approach is applied to the problem of secure communications and illustrated through numerical examples.